1997
DOI: 10.1111/j.1442-9071.1997.tb01272.x
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin in fourth nerve palsies

Abstract: BTXA is of greatest benefit in patients with residual deviations particularly when the inferior rectus is injected, but is of limited value as a primary therapy in chronic IV N palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Half of patients had improvement in their symptoms for primary and reading positions, and resolution of torticollis, but diplopia was not eliminated in lateral gaze positions (n ¼ 6). Garnham et al [25] reported that botulinum was most successful for superior oblique palsies when the inferior rectus was injected. When only the inferior oblique was injected 83% of patients ultimately did require surgery (n ¼ 20).…”
Section: Cranial Nerve Palsiesmentioning
confidence: 99%
“…Half of patients had improvement in their symptoms for primary and reading positions, and resolution of torticollis, but diplopia was not eliminated in lateral gaze positions (n ¼ 6). Garnham et al [25] reported that botulinum was most successful for superior oblique palsies when the inferior rectus was injected. When only the inferior oblique was injected 83% of patients ultimately did require surgery (n ¼ 20).…”
Section: Cranial Nerve Palsiesmentioning
confidence: 99%
“…1 Treatment for SOP commonly consists of surgical intervention since lateral incomitance often limits prism use, and botulinum toxin studies have not been encouraging for long-term improvement. 2 Vertical diplopia, torsional diplopia, or significant torticollis are all indications for surgery. A number of operative techniques have been recommended for the treatment of SOP including weakening the ipsilateral inferior oblique, 37 contralateral inferior rectus recession, 8 ipsilateral superior rectus recession, 9 and superior oblique tuck, isolated or in combination.…”
Section: Introductionmentioning
confidence: 99%
“…1,4,[10][11][12] The magnitude of visual disturbance can also be evaluated more objectively using prisms. In one study 13 the mean vertical deviation of 20 patients (aged 19-70 years) with congenital or traumatic fourth CN palsy was 11 prism diopters. In this patient, the diplopia was both vertical and torsional, with left gaze being off by 20 prism diopters at 5 weeks postinjury.…”
Section: Discussionmentioning
confidence: 96%